2012
DOI: 10.5194/acpd-12-25983-2012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aerosol classification by airborne high spectral resolution lidar observations

Abstract: During four aircraft field experiments with the DLR research aircraft Falcon in 1998 (LACE), 2006 (SAMUM-1) and 2008 (SAMUM-2 and EUCAARI), airborne High Spectral Resolution Lidar (HSRL) and in situ measurements of aerosol microphysical and optical properties were performed. Altogether, the properties of six different aerosol types and aerosol mixtures – Saharan mineral dust, Saharan dust mixtures, Canadian biomass burning aerosol, African biomass burning aerosol, anthropogenic pollution aerosol, and ma… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 74 publications
3
16
0
Order By: Relevance
“…The main goal of this study was to determine lidar derived optical properties for European pollution aerosols, in particular the particle linear depolarization ratio and the lidar ratio. Both quantities are independent from the aerosol load and, in combination, have the potential to distinguish different aerosol types as was recently shown by Groß et al (2011Groß et al ( , 2012 and Burton et al (2012).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The main goal of this study was to determine lidar derived optical properties for European pollution aerosols, in particular the particle linear depolarization ratio and the lidar ratio. Both quantities are independent from the aerosol load and, in combination, have the potential to distinguish different aerosol types as was recently shown by Groß et al (2011Groß et al ( , 2012 and Burton et al (2012).…”
Section: Discussionmentioning
confidence: 92%
“…This paper focuses on the analysis of the airborne HSRL measurements of the aerosol lidar ratio and the particle linear depolarisation ratio taken during the first half of EUCAARI-LONGREX (6 May to 14 May). Both quantities only depend on the aerosol type and can be used to classify different types of aerosol (Groß et al, 2011(Groß et al, , 2012Burton et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Both L2‐1 and L2‐2 were likely influenced by aged smoke from BB due to their relatively low backscatter and low depolarization. The linear depolarization of aged smoke can be lower than fresh smoke [ Burton et al, ; Gro ß et al, ] because the scavenging and deposition processes remove some of the large and nonspherical particles during transport. However, ozone enhancements due to BB alone will rarely reach 30 ppbv [e.g., Real et al, ; Parrington et al ., ] even when ozone production is very efficient at a low NO x concentration [ Hudman et al, ].…”
Section: Resultsmentioning
confidence: 99%
“…As demonstrated by Baars et al (), aerosol types can be identified by combining their Ångstrom exponent, lidar ratio, and depolarization ratio from multiwavelength HSRL or Raman‐polarization lidar measurements (Burton et al, ; Groß et al, ). Therefore, our study assumes known aerosol types for CCN retrievals for the sake of tackling other more challenging tasks in retrieving CCN profiles.…”
Section: Methodsmentioning
confidence: 99%
“…These can be retrieved from multiwavelength Raman lidar (Ansmann et al, ) or HSRL measurements (Shipley et al, ). Aerosol type, which can be identified from lidar measurements (Baars et al, ; Burton et al, ; Groß et al, ), provides the mean complex refractive index (Table ). Thus, retrieving six parameters ( σ f , N tf , r f , σ c , N tc , and r c ) for a bimodal size distribution from five known quantities ( β 355 , β 532 , β 1064 , α 355 , and α 532 ) is still an ill‐defined problem.…”
Section: Methodsmentioning
confidence: 99%